Geotechnical engineering design - Kozel, Petre (SCITUS Academics LLC, 2016)
Geotechnical engineering is the branch of civil engineering concerned with the engineering behavior of earth materials. Geotechnical engineering is important in civil engineering, but also has applications in military, mining, petroleum and other engineering disciplines that are concerned with construction occurring on the surface or within the ground. Geotechnical engineering uses principles of soil mechanics and rock mechanics to investigate subsurface conditions and materials; determine the relevant physical/mechanical and chemical properties of these materials; evaluate stability of natural slopes and man-made soil deposits; assess risks posed by site conditions; design earthworks and structure foundations; and monitor site conditions, earthwork and foundation construction. This book presents the fundamental design principles and approaches in geotechnical engineering. including an introduction to engineering geology, subsurface explorations, shallow and deep foundations, slope stability analyses and remediation, filters and drains, Earth retaining structures, geosynthetics, and bask seismic evaluations of slope stability, lateral earth pressures, and liquefaction. This book applies the principles of soil mechanics, earthquake and focuses on the design methodologies in geotechnical engineering.